Hadith #2543 - Sunan Abi Dawud - Abdul Quddus bin al-Hajjaj al-Khulani عبد القدوس بن الحجاج الخولاني; Aqeel bin Shubayb عقيل بن شبيب; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Muhammad bin Muhajir bin Abi Muslim محمد بن مهاجر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Keep to every dark bay horse with a white blaze and white on the legs, or sorrel with a white blaze and white on the legs , or black with a white blaze and white on the legs.
Grade: Da'if

Hadith #2547 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Abu Kabsha al-Saluli أبو كبشة السلولي; Mskyn bin Bkyr al-Hrany مسكين بن بكير الحراني أبو عبد الرحمن; Muhammad bin Muhajir bin Abi Muslim محمد بن مهاجر; Rabi'a bin Yazid al-Damashqi ربيعة بن يزيد الدمشقي; Sahl bin al-Rabi' bin 'Amr (Sunan Abi Dawud)
Abu Hurairah said “The Prophet (ﷺ) disapproved the shikal horses. Shikal are the horses that are white on their right hind leg and white on their left foreleg or white on their right foreleg and left hind leg. Abu Dawud said “This means alternate legs”.
Grade: Sahih

Hadith #3880 - Sunan Abi Dawud - al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; Asma' bint Yazid bin al-Sakan; Muhajir bin Abi Muslim; Muhammad bin Muhajir bin Abi Muslim محمد بن مهاجر (Sunan Abi Dawud)
The man casting evil would be commanded to perform ablution, and then the man affected was washed with it.
Grade: Da'if